2015
DOI: 10.1007/s11277-015-2807-2
|View full text |Cite
|
Sign up to set email alerts
|

EACHP: Energy Aware Clustering Hierarchy Protocol for Large Scale Wireless Sensor Networks

Abstract: Wireless sensor networks (WSNs) comprise a large number of small sensor nodes scattered across limited geographical areas. The nodes in such networks carry sources of limited and mainly unchangeable energy. Therefore, it is necessary that these networks operate under energy efficient protocols and structures. Energy efficient clustering algorithms have been developed to reduce the networks energy consumption and extend its lifetime. This paper presents an innovative cluster-based communication protocol for WSN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The signal is transmitted over the air and received at the sensor nodes [17,18] within the monitoring area. During the transmission, the signal is attenuated by environmental factors such as physical obstacles, which would lead to uncertainty for the received signal at the sensor nodes [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…The signal is transmitted over the air and received at the sensor nodes [17,18] within the monitoring area. During the transmission, the signal is attenuated by environmental factors such as physical obstacles, which would lead to uncertainty for the received signal at the sensor nodes [19][20][21].…”
Section: Methodsmentioning
confidence: 99%
“…Five state-of-the-art methods were then compared and the results showed that this approach greatly extends the network life. Barati et al 17 presented an Energy Aware Clustering Hierarchy Protocol to reduce the communication overhead. A multi-level hierarchical structure was created to adequately route and collect data in WSNs.…”
Section: Related Workmentioning
confidence: 99%
“…The second phase is the steady-state phase responsible for data transmission between the nodes and CHs, and between the CHs and base station (BS) [15].…”
Section: Leachmentioning
confidence: 99%
“…o t h e r w i s e (15) where r is the number of the current round, G the set of the nodes that have not become cluster heads within the last 1 pnrm round, and G the set of nodes that have not become cluster heads within the last 1 p adv round.…”
Section: Sepmentioning
confidence: 99%